Diaspora, politics, and globalization - Laguerre, Michel S. (Palgrave Macmillan, 2006)
Laguerre proposes a relationship among migrants and their home society that transcends current views in migration studies. The relationship among Haitians who live outside Haiti reflects a web rather than a radial relationship with the home country; Haitian migrants communicate among themselves and the home country simultaneously. In viewing the Haitian diaspora from a global perspective, the author reveals a new theory of interconnectedness in migration, which marks a significant move away from transnationalism